Base pair opening dynamics of a 2-aminopurine substituted Eco RI restriction sequence and its unsubstituted counterpart in oligonucleotides. - Lycksell, P O (1987)
Studies of 1H NMR selective saturation recovery were performed to determine the imino proton exchange with solvent water of the base pairs in the Eco RI endonuclease recognition sequence GAATTC, placed at the center of self-complementary decamer and dodecamer oligonucleotides. In one oligonucleotide the innermost adenine was replaced by the fluorescent base analogue 2-aminopurine (2AP). From the measurements at different concentrations of TRIS buffer acting as proton exchange catalyst, base pair lifetimes were evaluated. The results at 25 degrees show that the AT base pairs have lifetimes of the order of a few ms, whereas the surrounding GC base pairs in a dodecamer have lifetimes of about 100 ms. The (2AP)T base pair has a shorter lifetime than the corresponding AT base pair. The temperature dependent optical absorption, and for the 2AP containing oligonucleotide fluorescence, were used to study the single strand-duplex equilibrium of the decamers. The results indicate that NMR and the optical techniques, although applied at very different concentrations, monitor the same conformational transition of the oligonucleotide.